Gut Microbiota and the Gut–Liver Axis in Liver Disease: From Chronic Viral Hepatitis to Cirrhosis, Hepatocellular Carcinoma, and Microbiome-Based Therapies - Sniedze Laivacuma; Olga Oblate; Aleksejs Derovs (Microorganisms)
Chronic viral hepatitis B and C remain major global health challenges, contributing significantly to liver-related morbidity and mortality. Despite antiviral therapies and vaccines for HBV, progression to cirrhosis and hepatocellular carcinoma remains common. For HCV, the lack of a vaccine and high chronicity rates further complicate outcomes. Recent evidence highlights gut–liver axis dysfunction and microbiota dysbiosis in disease progression, immune dysregulation, and fibrosis. Notably, alterations in microbiota composition, including reduced commensal bacteria such as Bifidobacteria and Lactobacilli and an increase in putatively harmful Enterobacteriaceae and Veillonellaceae, have been observed in HBV/HCV infections and cirrhosis. While antiviral therapies do not directly target the gut microbiota, they can contribute to partial restoration of microbial balance by reducing hepatic inflammation and improving gut–liver axis integrity. Nonetheless, post-treatment patients remain at elevated risk of HCC due to persistent epigenetic and immune-mediated changes. Emerging interventions, including probiotic strains, prebiotics, and symbiotics, demonstrate potential in enhancing gut health, alleviating inflammation, and enhancing the quality of life for liver disease patients. Moreover, the gut microbiota is gaining increasing recognition as a potential non-invasive biomarker for early disease detection and monitoring. Ultimately, modulating the gut microbiota could become an integral component of future strategies for managing chronic liver diseases and preventing their complications.